2021
DOI: 10.1111/jgs.17495
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to promote dementia knowledge among racial/ethnic minority groups: A systematic review

Abstract: Background Certain racial/ethnic minority groups have a higher risk of developing dementia, yet studies have demonstrated that they often have limited knowledge and understanding of this disease. An increasing number of educational and advocacy programs have been developed to promote dementia knowledge. We aimed at assessing current evidence and quality regarding educational interventions for promoting dementia knowledge. Methods We searched for intervention studies published in English that focused on educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
(267 reference statements)
0
21
0
Order By: Relevance
“…Both the quantitative and qualitative findings suggest that caregivers reported increased knowledge of dementia after participating SCP Plus. These findings are promising, as research suggests that there is a continued need for interventions that promote knowledge of ADRD among racial and ethnic minority groups [ 54 ]. Previous research also points toward the need for, and benefits of, improving knowledge of ADRD among ethnically diverse ADRD caregivers [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both the quantitative and qualitative findings suggest that caregivers reported increased knowledge of dementia after participating SCP Plus. These findings are promising, as research suggests that there is a continued need for interventions that promote knowledge of ADRD among racial and ethnic minority groups [ 54 ]. Previous research also points toward the need for, and benefits of, improving knowledge of ADRD among ethnically diverse ADRD caregivers [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…While those education campaigns had not eliminated the stigma around dementia, we speculate that the programs focusing on Black churches and community centers may have reduced the impact of stigma among the Black older adults in our sample. This project highlighted the depth of misunderstanding and stigma associated with dementia in minority and lower income communities, and emphasized the need for continuing and long-term ongoing education about dementia and resources available to families dealing with dementia (Epps et al, 2018; Huggins et al, 2021; Laditka et al, 2013; Parker et al, 2020). Finally, our findings echo previous research documenting racial disparities in cognition scores.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this project, the county AAA has added the Mini-Cog™ instrument to their intake procedures for CMs serving vulnerable communities across the county. Future interventions to encourage the acceptance of Mini-Cog™ screenings in non-clinical settings, as well as acceptance of referrals for additional evaluation of cognitive function, should begin with reducing stigma in the community by educating the public about dementia and engaging members of racial and cultural communities in outreach (Huggins et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, older adults and caregivers need to recognize the importance of early dementia screening. Previous studies reported the need for community education and the significant impact of dementia on the quality of life among older adults and their caregivers; therefore, communities should play a role in advocacy to encourage early dementia screening in older adults 33,35 . Screening procedures for dementia in older adults should fully consider each patient's current health status and choose a method that is acceptable to both patients and their families.…”
Section: Discussionmentioning
confidence: 99%